PARALINGUISTIC REPRESENTATION AND FORMATION OF RELIGIOUS CONCEPTS IN ENGLISH AND UZBEK LANGUAGES: A LINGUOCOGNITIVE ANALYSIS - Ikromova Durdonaxon (TADQIQOTLAR, 2026)
Abstract: This article explores the role of paralinguistic features in the formation and representation of religious concepts in English and Uzbek languages from a linguocognitive perspective. Paralinguistics, including intonation, pitch, rhythm, pauses, and voice quality, plays a significant role in conveying implicit meanings and emotional attitudes in religious discourse. The study examines how these non-verbal elements contribute to the conceptualization of religious ideas and values within different linguistic and cultural contexts. By comparing English and Uzbek religious communication, the research identifies similarities and differences in the use of paralinguistic means and their influence on cognitive perception. The findings demonstrate that paralinguistic features are essential in shaping religious understanding and enhancing communicative effectiveness.